Analysis of the Effect of Work Discipline, Quality Standards And Financial Compensation for Teacher Performance - Susan Grace V Nainggolan; Asianna Martini Simarmata (Jurnal Ekonomi, 2023)
This study aims to study the effect of work discipline, quality standards and financial compensation on teacher performance. The three independent variables in this study are work discipline (X1), quality standards (X2) and financial compensation (X3), while the dependent variable is teacher performance (Y). There were 25 respondents from a total of 50 populations. Multiple regression analysis method is the right method used in this study. The goal is to identify current issues and convey attitudes that are consistent with known facts. The research findings show that simultaneously the existence of work discipline, quality standards and financial compensation can significantly worsen teacher performance with the results Fcount > Ftable (65.443 > 2.72) or in a percentage of 71.6%.